Indication of laparoscopic liver resection - Morise, Zenichi (Laparoscopic Surgery, 2018)
Laparoscopic liver resection (LLR) began with the initial publications in 1991 and 1992 (1). In terms of the style of procedures, LLR was first introduced to the partial resection of the anterolateral segments (easy access area under laparoscope; segments 2, 3, caudal part of 4, 5, 6). The reports of left lateral sectionectomy followed in 1996 (2).